2020
DOI: 10.1101/2020.03.23.20041665
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spectral Clustering of Risk Score Trajectories Stratifies Sepsis Patients by Clinical Outcome and Interventions Received

Abstract: Sepsis is not a monolithic disease, but a loose collection of symptoms with a diverse range of outcomes. The diverse patterns of sepsis make guideline-driven treatment difficult, as guidelines are based on the needs of the "average" patient. Thus, stratification and subtyping of sepsis patients is of interests, with the ultimate goal of identifying groups of patients who respond similarly to treatment. To do this, we examine the temporal evolution of patient state using our previously-published method for comp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…Sepsis has been found to be consisted of several phenotypes, though specific class membership assignments are different across studies [12][13][14][15][16][17][18]. By using clinical trial data from 1696 patients, Gårdlund B and colleagues identified six classes of septic shock [19].…”
Section: Introductionmentioning
confidence: 99%
“…Sepsis has been found to be consisted of several phenotypes, though specific class membership assignments are different across studies [12][13][14][15][16][17][18]. By using clinical trial data from 1696 patients, Gårdlund B and colleagues identified six classes of septic shock [19].…”
Section: Introductionmentioning
confidence: 99%
“…We repeated our analyses of risk score trajectories for stratification of sepsis patients 15 on the SEQUIP dataset. Spectral clustering 21 of risk score trajectories in the window surrounding early prediction yielded two clusters (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, using spectral clustering of patient risk score trajectories, we further elucidated the pre-shock state, finding that entry into the state was marked by a rapid transition from low to high risk. Prior to entry, sepsis patient physiology was indistinguishable between the low and high risk clusters of patients 15 . However, after the occurrence of this event, patient risk trajectories diverged, and stratified patients by risk of septic shock, mortality, time to septic shock onset, and treatments received.…”
Section: Stratification Of Patientsmentioning
confidence: 98%
See 2 more Smart Citations